Optimalisasi Pola Operasi Tanpa Penambahan Alat Untuk Meningkatkan Produksi Pada Industri Kertas - Ependi, Ujang Rahmat; Putranto, Kartiko Eko (Universitas Pamulang, 2024)
From the data analyzed, it is known that the problems being faced by paper production companies, especially PT. XYZ is the amount of production produced during the paper production process in 2019 which has made the company suffer a total loss of 4,876 tons. This thesis aims, firstly to find out how to measure productivity in the latest paper industry, second what are the ways to optimize productivity, third what are the causes of productivity in the paper industry is not optimal, fourth how to determine how to optimize productivity most efficiently.To achieve these objectives, this thesis uses the OEE (Overall Equipment Effectiveness) method in increasing the cutsize sheeter. The cutsize sheeter was chosen in this study because the cutsize sheeter has a lower yield than the predetermined target.The results of the calculation of OEE value on the cutsize sheeter in 365 days are 31.29%) <85% (world standard OEE values). Two variables that cause low OEE values ​​are time efficiency and performance efficiency.The results of the calculation of the OEE Big Losses Value on the cut size sheeter are Reduce Speed ​​Loss of 45.45%, Breakdown Loss of 21.54%. Furthermore, technical analysis with the company efficiency team, using a fishbone diagram to identify the causes of the problem (why), identify the causes of the problem (how). The next step is to apply the Plan - do - check - action method to find the root of the problem and make quality improvements. Result, this thesis suggests 1). Performance, especially low speed, can be overcome by working with the HRD team in conducting training, 2). The problem of high breakdown can be overcome by improving communication between the dept. engineering, 3). For base papers that do not fit the deckle, coordinate with the Dept. Finishing & PPIC